2012
DOI: 10.1083/jcb.201204010
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into WHAMM-mediated cytoskeletal coordination during membrane remodeling

Abstract: Structural analysis of the WHAMM–microtubule interaction provides insight into WHAMM’s coordination of microtubule binding, membrane association, and actin nucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…Thus, the middle region of WHAMM (aa 174–541), implicated in MT binding [17], seems to be at least in part responsible for this phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the middle region of WHAMM (aa 174–541), implicated in MT binding [17], seems to be at least in part responsible for this phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Similar images are also obtained with other MT-binding proteins, although their biochemical analyses and established biological functions do not involve a high degree of cooperativity. 34,37 It seems likely that a high heterogeneity of MT decoration reported by cryo-electron microscopy might be an artifact of some aspect of a sample preparation procedure. Our experimental work with GFP-labeled NDC80 proteins shows the homogeneous decoration of MTs when experiments are carried out with reagents that block the non-specific protein binding to a surface of microscopy chamber, but highly heterogeneous MT decoration is seen when such blocking reagents are omitted (unpublished observation).…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have shown that RhoD interacts with WHAMM to regulate Golgi structure and the transport of cargo to the plasma membrane (Blom et al, 2015;Gad et al, 2012). Cryoelectron microscopy revealed that WHAMM binds to the outer surface of MT protofilaments via its CC domain and forms helical head-to-tail structures along MTs (Shen et al, 2012). MT binding induces a structural change that exposes the N-terminal WMD for membrane binding and tubulation activity, while masking the C-terminal WWCA motif, thus preventing actin polymerization (Liu et al, 2017).…”
Section: Regulation and Cytoplasmic Functions Of Whamm Jmy And Wash mentioning
confidence: 99%